Current issues - Forbes, David; Wongthongtham, Pornpit; Terblanche, C.; Pakdeetrakulwong, U. (2018)
This book is designed to provide a philosophical perspective brief on what may be regarded as a conceptual ecosystem as an example of information systems and knowledge management modelling.